Management of peripheral arterial disease in the elderly: focus on cilostazol - Falconer, Travis M (Dove Medical Press, 2008)
Symptomatic and asymptomatic peripheral arterial disease (PAD) is a common problem in the elderly. The management of PAD includes the prevention of cardiovascular events and relief of symptoms – most commonly intermittent claudication (IC). Both require treatment of the causes and consequences of atherothrombosis, but some strategies are more effective for prevention of cardiovascular events and others are more effective for the relief of symptoms. Priorities for the prevention of cardiovascular events include smoking cessation, exercise, antiplatelet therapy, and the treatment of dyslipidemia, hypertension, and diabetes. Walking time and ability are improved by exercise. The benefit of numerous drugs in the treatment of IC has been assessed. The results have generally been disappointing, but there is some evidence that statins and cilostazol (an inhibitor of phosphodiesterase 3) are of benefit. Meta-analyses suggest that cilostazol increases maximum walking distance by 40%–50% and improves other objective measures of walking. The safety profile of cilostazol in patients with PAD appears to be acceptable although the mechanism for its effect on IC is unclear. In addition to risk factor management, treatment with cilostazol should be considered in patients with disabling IC.